DIGITAL SHARIA INSURANCE INNOVATION: A CASE STUDY OF KITABISA INSURANCE PLATFORM AND ITS IMPACT ON FINANCIAL INCLUSION IN INDONESIA - Sunendar, Suryo Anugrah; Aditya, Chika (JURNAL ASIK, 2025)
This study aims to analyze the application of sharia principles and technological innovation in the business model of Kitabisa Insurance, a digital insurance platform based on mutual cooperation. This study explores how this platform improves financial inclusion through affordable, transparent, and solidarity-based services. Using a qualitative method based on case studies, data was collected through interviews, observations, and documentation. The results of the study show that Kitabisa Insurance has succeeded in answering the challenge of low penetration of sharia insurance in Indonesia by expanding accessibility and increasing financial literacy in the community. The technological innovations implemented make it easier for users to register, contribute, and claim, while building trust through data transparency. This study contributes to the development of digital-based sharia insurance services.